Transsulfuration pathway activation attenuates oxidative stress and ferroptosis in sickle primary erythroblasts and transgenic mice - Caixia Xi; Junfeng Pang; Weinan Xue; Yang Cui; Na Jiang; Wenbo Zhi; Huidong Shi; Anatolij Horuzsko; Betty S. Pace; Xingguo Zhu (Communications Biology)
Abstract The transsulfuration (TSS) pathway is an alternative source of cysteine for glutathione synthesis. Little of the TSS pathway in antioxidant capacity in sickle cell disease (SCD) is known. Here, we evaluate the effects of TSS pathway activation through cystathionine beta-synthase (CBS) to attenuate reactive oxygen species (ROS) and ferroptosis stresses in SCD. A vital contribution of the TSS pathway in sustaining cysteine levels is detected only under hemin exposure or physiological but not supraphysiological cystine supplement. Mechanistic studies show that hemin suppresses CBS expression to inhibit the TSS pathway and de novo cysteine biosynthesis. By contrast, the expression of CBS is inducible by dimethyl fumarate (DMF) through nuclear factor erythroid 2-related factor 2 (NRF2) activation and CpG islands DNA hydroxymethylation. DMF induces the expression of L-2-hydroxyglutarate dehydrogenase (L2HGDH) to downregulate L-2-hydroxyglutarate (L2HG) and increase global and locus-specific DNA hydroxymethylation levels. This DMF-upregulated DNA hydroxymethylation affects CBS locus chromatin structure modifications and upregulates gene expression. Our results suggest that CBS of the TSS pathway plays an important role in maintaining cysteine levels under restricted cystine availability or excess hemin exposure, and CBS upregulation by DMF increases the cellular glutathione levels to protect against ROS and ferroptosis stress in SCD.